Participatory Election Supervision Education Model for Strengthening Bawaslu Capacity: A Systematic Literature Review - Zamharil Zamharil; Rizky Firnanda; Tukini Rahmawati (Sakura Digital Nusantara, 2026)
Participatory election supervision is an important strategy for strengthening democracy and improving the institutional capacity of Bawaslu. This study aims to analyze the participatory election supervision education model in strengthening Bawaslu’s capacity through a Systematic Literature Review (SLR) approach. The literature review process was conducted through several stages, including identification, screening, eligibility assessment, and final analysis of 30 relevant scientific articles from various publication sources. The findings indicate that the participatory election supervision education model contributes to improving public electoral literacy, expanding supervision networks, strengthening citizen participation, and enhancing public trust in Bawaslu. The model is also supported by educational management functions, including planning, organizing, implementation, and evaluation. However, the implementation of this model still faces several challenges, including the sustainability of community participation, digital literacy gaps, coordination among stakeholders, and strengthening evaluation mechanisms. This study concludes that participatory election supervision education can serve as a strategic approach to strengthening Bawaslu’s institutional capacity through a collaborative, inclusive, and sustainable democratic education framework.